An exploratory analysis on Kayamandi as a sustainability conundrum : identifying the missing links towards a more sustainable future - Petzer, Kyle John (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015.